PEMBERIAN PUPUK ORGANIK CAIR LIMBAH TAHU DALAM MEDIA HIDROPONIK RAKIT APUNG TERHADAP PERTUMBUHAN TANAMAN SAWI HIJAU (Brassica juncea L.) - Andhini Aprilia; Elvi Rusmiyanto Pancaning Wardoyo; Mukarlina Mukarlina (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
The content of protein, fiber, vitamins, and fat contained in mustard greens (B. juncea) is the main attraction for people to consume vegetables. Green mustard plant growth using hydroponic media can help optimize the absorption of nutrients needed by plants. The application of the floating raft hydroponic method with the addition of liquid organic fertilizer from tofu liquid waste is an effort that is expected to overcome this problem. This research to determine the impact and concentration of POC tofu liquid waste which has the best impact on the growth of green mustard plants. Use of RAL with 6 levels of treatment, namely P1=0%POC; P2 = 35%POC; P3 = 40%POC; P4 = 45%POC; P5 = 50%POC; P6 = 55%POC. Data were analyzed using ANOVA with a 95% confidence level. The application of liquid organic fertilizer significant impact on measuring plant height, number of leaf blades, leaf surface area, root shoot wet weight, root shoot dry weight, and chlorophyll. The best liquid organic fertilizer treatment of tofu waste was the concentration of 55% for plant height (31.72 cm), number of leaves (13.50), leaf area (1287 mm), crown wet weight (65.95 g), wet weight root (2.97 g), shoot dry weight (37.8 g), root dry weight (1.25 g), chlorophyll a content (24.74 mg/g), b (30.54 mg/g) and total (52.40 mg/g).